KARAKTERISTIK KIMIA KONJUGAT ISOLAT PROTEIN KEDELAI-LAKTOSA YANG BERPOTENSI DALAM PENURUNAN ALERGENISITAS - Muhammad Hasriandy Asyhari; Nurheni Sri Palupi; Didah Nur Faridah (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2018)
Soy protein isolate (SPI) is a product from soybeans with great functionality thus is widely used as an ingredient in any formulation by food and beverage industries. Glycation is commonly done to improve protein functionality and reduce its allergenicity. This research aims to analyze the influence of incubation time of SPI and lactose on the degree of glycation of SPI-lactose conjugates, free amino acid and lactose bases, and to identify the molecular weight and intensity of the protein band of the SPI-lactose conjugate. SPIs were obtained by pH adjustment. The glycation of SPI and lactose was undertaken at pH 9.5, 95°C for 0, 30, 60 and 90 minutes. The determination of the glycation degree of the SPI-lactose conjugate was carried out using several methods, i.e. TBA-based method, HPLC and Bradford analysis. The profiles of the protein molecular weight was analyzed using SDS-PAGE. The results revealed that longer incubation time induced a greater degree of glycation. SDS-PAGE showed that the soybean sample had 13 protein bands with molecular weights ranging from 11.8 to 170.2 kDa. Glycation of SPI with lactose at 95°C could remove or lower the intensity of protein bands with molecular weight of 66.6; 56.1 and 30.9 kDa, which were presumed to be the major allergens in soybean.